Divergently Transcribed ncRNAs in Escherichia coli: Refinement of the Transcription Starts Assumes Functional Diversification - Kiselev, Sergey; Markelova, Natalia; Masulis, Irina (Frontiers in Molecular Biosciences, 2021)
Non-coding regulatory RNAs (ncRNAs) comprise specialized group of essential genetically encoded biological molecules involved in the wide variety of cellular metabolic processes. The progressive increase in the number of newly identified ncRNAs and the defining of their genome location indicate their predominant nesting in intergenic regions and expression under the control of their own regulatory elements. At the same time, the regulation of ncRNA’s transcription cannot be considered in isolation from the processes occurring in the immediate genetic environment. A number of experimental data indicate the notable impact of positional regulation of gene expression mediated by dynamic temporal DNA rearrangements accompanying transcription events in the vicinity of neighboring genes. This issue can be perceived as particularly significant for divergently transcribed ncRNAs being actually subjected to double regulatory pressure. Based on available results of RNAseq experiments for Escherichia coli, we screened out divergent ncRNAs and the adjacent genes for the exact positions of transcription start sites (TSSs) and relative efficiency of RNA production. This analysis revealed extension or shortening of some previously annotated ncRNAs resulting in modified secondary structure, confirmed stable expression of four ncRNAs annotated earlier as putative, and approved the possibility of expression of divergently transcribed ncRNAs containing repetitive extragenic palindromic (REP) elements. The biogenesis of secreted ncRNAs from divergently transcribed ffs, chiX, ralA, and ryhB is discussed taking into account positions of TSSs. Refinement of TSSs for the neighboring genes renders some ncRNAs as true antisense overlapping with 5′UTR of divergently transcribed mRNAs.